(untitled) (Anclajes, 2016)
The International Congresses of the Spanish Language (CILEs) encompass one of the main discursive mechanisms for disseminatintg the Pan-Hispanic linguistic policy implemented by Spain in recent decades. These public events promote a homogeneous discourse about the Spanish language, and seek to create a space of acceptance as well as promote linguistic instruments presented as applicable across to the Hispanic field. Within this framework, we consider that the CILEs form part of an ideological discursive matrix whose central tenets can be found in a preceding congress held as early as 1892. Also, some components of this matrix are included in a broader matrix, and are evident in various discourses from the end of the nineteenth century up to the present, with some modifications due to contextual changes. These discourses favor the conservation of linguistic unity in the Hispanic community, and highlight the apparently “natural” leadership of the Iberian Peninsula with respect to Latin American countries in matters of linguistic authority.